Synergy of Ethical Leadership and Emotional Intelligence to Increase Employee Job Satisfaction - Muharti; Albafery; Darimi (Indonesian Journal of Business Analytics, 2026)
This study aims to analyze the synergy of ethical leadership and emotional intelligence in improving employee job satisfaction. The research location was at the Garuda Health Center in Pekanbaru City with a sample of 44 employees selected through accidental sampling techniques. The data was analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with the help of SmartPLS software. The results showed that ethical leadership had a significant positive effect on job satisfaction (original sample = 0.503; p = 0.000), and emotional intelligence also had a significant positive effect on job satisfaction (original sample = 0.469; p = 0.000). The combination of these two variables forms an effective synergy model with a contribution of 78.2%. These findings indicate that the culture of leaders' discussions in solving problems and listening to subordinate input is able to generate optimal employee job satisfaction.